2019
DOI: 10.1186/s12967-019-1829-z
|View full text |Cite|
|
Sign up to set email alerts
|

Delivery of oncolytic vaccinia virus by matched allogeneic stem cells overcomes critical innate and adaptive immune barriers

Abstract: Background Previous studies have identified IFNγ as an important early barrier to oncolytic viruses including vaccinia. The existing innate and adaptive immune barriers restricting oncolytic virotherapy, however, can be overcome using autologous or allogeneic mesenchymal stem cells as carrier cells with unique immunosuppressive properties. Methods To test the ability of mesenchymal stem cells to overcome innate and adaptive immune barriers and to successfully deliver on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 84 publications
(79 reference statements)
0
21
0
Order By: Relevance
“… 10 MSCs were used for delivering measles virus, 13 , 14 herpes simplex virus, 15 adenovirus, 16 and vaccinia virus. 17 Here, we used human bone-marrow-derived MSCs to deliver recombinant oncolytic myxoma virus (MYXV).…”
Section: Introductionmentioning
confidence: 99%
“… 10 MSCs were used for delivering measles virus, 13 , 14 herpes simplex virus, 15 adenovirus, 16 and vaccinia virus. 17 Here, we used human bone-marrow-derived MSCs to deliver recombinant oncolytic myxoma virus (MYXV).…”
Section: Introductionmentioning
confidence: 99%
“…Ex-vivo-expanded hypoimmunogenic human adipose-derived stem cells (ADSCs) represent a unique delivery platform for OVs. They combine a natural capacity to home to inflammatory sites with a tumor tropism that is coupled with potent amplification of the OV load and transient suppression of anti-viral innate immunity, which hinders OVs from colonizing the tumor site and infecting cancer cells [ 33 ]. Importantly, IFNγ, which is involved in the induction of an anti-viral state, also modulates immunosuppressive features of ADSCs, counteracting anti-viral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we showed that the therapy targeting experimentally induced lung melanoma in mice with IL-15-encoding MYXV construct (vMyx-IL15Rα-tdTr) delivered by MSCs was effective and was able to reduce the tumor burden as well as triggering the inflow of CD8+ cells [ 33 ]. Here, we demonstrate another ADSC-shielded recombinant MYXV that expresses LIGHT protein, used to extend the survival of treated mice and to increase the influx of T lymphocytes into the tumor.…”
Section: Discussionmentioning
confidence: 99%
“… 27 High costs associated with loading cells with OVs ex vivo may be reduced using off-the-shelf, allogeneic stem cells. 30 Delivery of OVs using cellular carriers is already being investigated in the clinical arena. 34 For instance, MSCs loaded with AdV were shown to be safe in pediatric and adult solid tumors.…”
Section: Shielding Ovs From the Innate And Adaptive Humoral Immunitymentioning
confidence: 99%